Association among occupational class, alcohol consumption, and the risk of hospitalisations due to alcoholic liver diseases: a matched case-control study - Shoko Nakazawa; Yuko Furuya; Kosuke Sakai; Kota Fukai; Kei Sano; Keika Hoshi; Noriko Kojimahara; Akihiro Toyota; Masaaki Korenaga; Masayuki Tatemichi (BMC Public Health)
Abstract Background This study aimed to identify the occupational class and specific occupations associated with hospitalisations due to alcohol-related liver disease and alcoholic liver cirrhosis, based on the distribution of alcohol consumption. Methods This matched case-control study used a nationwide, multicentre, inpatient dataset from the Inpatient Clinico-Occupational Database of the Rosai Hospital Group in Japan. A total of 5,490 cases with alcohol-related liver disease and 10,961 controls were included in this study. Participants were categorised according to occupational class (blue-collar, service, professional, and manager) and industrial sector (blue-collar, service, and white-collar). Professionals in white-collar industries were set as the reference group. We calculated the odds ratios (ORs) and confidence intervals (CIs) of alcohol-related liver disease and alcoholic liver cirrhosis using conditional logistic regression models. Results Blue-collar workers and service workers in both the service and blue-collar industries had a higher risk of hospitalisations due to alcohol-related liver disease: The ORs (95% CIs) for alcohol-related liver disease were 1.33 (1.15–1.55) for blue-collar workers in the blue-collar industry, 1.21 (1.03–1.42) for service workers in the blue-collar industry, 1.23 (1.01–1.51) for blue-collar workers in the service industry, and 1.47 (1.25–1.72) for service workers in the service industry. Among service workers, food and drink preparatory workers and customer service workers had a higher risk of hospitalisations due to alcohol-related liver disease and alcoholic liver cirrhosis compared to professionals (reference group), with ORs of 2.28 (1.81–2.89) and 2.18 (1.64–2.89), respectively, for alcohol-related liver disease. Among blue-collar workers, skeleton construction workers had a higher risk of hospitalisations due to alcohol-related liver disease, with an OR of 2.31 (1.63–3.3). Workers in occupations with a high risk of hospitalisations due to alcohol-related liver disease had higher percentages of alcohol consumption compared to professionals. Conclusions Occupational class and specific jobs were associated with the risk of hospitalisations due to alcohol-related liver disease and alcoholic liver cirrhosis, with alcohol consumption patterns contributing to this increased risk.